2008
DOI: 10.1590/s1807-59322008000300015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methylprednisolone And Ganglioside GM-1 on a Spinal Lesion: A Functional Analysis

Abstract: Carvalho MOP, Barros Filho TEP, Tebet MA. Effects of methylprednisolone and ganglioside gM-1 on a spinal lesion: a functional analysis. Clinics. 2008;63:375-80. OBJECTIVES:The pharmacological effects of methylprednisolone (MP) and ganglioside gM-1 on spinal injuries have been thoroughly investigated, but only a few studies have evaluated the interaction between these two drugs. METHODS: Twenty-four Wistar rats were subjected to contusive injury of the spinal cord produced by the NYU system. These animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
0
11
0
7
Order By: Relevance
“…GM1 is a key glycosphyngolipid of mammalian nervous tissue, constituting the major subclass of brain gangliosides with effects on neural differentiation and repair processes, acting on the burgeoning and growth of in vivo and in vitro neurites. [13][14][15][16][17][18] Exogenous GM1 is incorporated to neuronal membranes and would have a enhancing action on neurotrophic factors. [13][14][15][16][17][18] Recent studies have demonstrated its effectiveness in helping functional repair in cases of diabetic peripheral neuropathy, stroke and acute rachimedullary trauma in humans and animals.…”
Section: Qualitative Histologymentioning
confidence: 99%
See 4 more Smart Citations
“…GM1 is a key glycosphyngolipid of mammalian nervous tissue, constituting the major subclass of brain gangliosides with effects on neural differentiation and repair processes, acting on the burgeoning and growth of in vivo and in vitro neurites. [13][14][15][16][17][18] Exogenous GM1 is incorporated to neuronal membranes and would have a enhancing action on neurotrophic factors. [13][14][15][16][17][18] Recent studies have demonstrated its effectiveness in helping functional repair in cases of diabetic peripheral neuropathy, stroke and acute rachimedullary trauma in humans and animals.…”
Section: Qualitative Histologymentioning
confidence: 99%
“…[13][14][15][16][17][18] Exogenous GM1 is incorporated to neuronal membranes and would have a enhancing action on neurotrophic factors. [13][14][15][16][17][18] Recent studies have demonstrated its effectiveness in helping functional repair in cases of diabetic peripheral neuropathy, stroke and acute rachimedullary trauma in humans and animals. [13][14][15][16][17][18] Previous studies have evidenced that the local administration of gangliosides at the repair site of a peripheral nerve injury produces an increased number of regenerated myelinized fibers.…”
Section: Qualitative Histologymentioning
confidence: 99%
See 3 more Smart Citations